PENGARUH TRAIT KEPRIBADIAN TERHADAP PENYESUAIAN PERKAWINAN PADA DEWASA AWAL USIA PERKAWINAN 1-5 TAHUN - Siti Shella; Anna Armeini Rangkuti (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2013)
Abstract The study was conducted to determine the effect of personality trait on marital adjustment in early adulthood. The personality trait based on The Big Five Factors of Personality theory by McCrae dan Costa. This study used a quantitative research method with a ex post facto design. The sample used in this study is 100 persons. The sampling technique used accidental sampling method. This study used two instruments were adopted from International Personality Item Pool Representation of The NEO PI-R (IPIPNEO) for personality scale and Dyadic Adjustment Scale (DAS) for marital adjustment scale. Data analysis used regression analysis of 5 predictors technique. Based on the calculations, the value of F = 3.810 with a significance of 0.003 (p <0.05), suggested that there is a significant influence personality trait to marital adjustment in early adulthood. The influence of personality trait to marital adjustment in early adulthood that is obtained by Adjusted R Square is 0.124 which means personality trait affect marital adjustment in early adulthood individual by 12.4%, while the remaining percentage showed that there are other factors that influence marital adjustment on early adulthood beside personality trait. The study result suggested that only neuroticism domain has negative significant influence on marital adjustment with a -1.295 regression coefficient and 0.021 significance (p <0.05). Keyword: personality trait, big five factors of personality, marital adjustment